A prospective randomized trial comparing homologous and autologous fibrin sealants for the control of alveolar air leak - Kılıç, Burcu; Erşen, Ezel; Demirkaya, Ahmet; Kara, H. Volkan; Alizade, Nurlan; İşcan, Mehlika; Kaynak, Kamil; Turna, Akif (Journal of Thoracic Disease; Vol 9, No 9 (September 27, 2017): Journal of Thoracic Disease, 2017)
Background: Postoperative air leak is a common complication seen after pulmonary resection. It is a significant reason of morbidity and also leads to greater hospital cost owing to prolonged length of stay. The purpose of this study is to compare homologous sealant with autologous one to prevent air leak following pulmonary resection. Methods: A total of 57 patients aged between 20 and 79 (mean age: 54.36) who underwent pulmonary resection other than pneumonectomy (lobar or sublobar resections) were analyzed. There were 47 males (83%) and 10 females (17%). Patients who intraoperatively had air leaks were randomized to receive homologous (Tisseel; n=28) or autologous (Vivostat; n=29) fibrin sealant. Differences among groups in terms of air leak, prolonged air leak, hospital stay, amount of air leak were analyzed. Results: Indications for surgery were primary lung cancer in 42 patients (71.9%), secondary malignancy in 5 patients (8.8%), and benign disease in 10 patients (17.5%). Lobectomy was performed in 40 patients (70.2%), whereas 17 patients (29.8%) had wedge resection. Thirteen (46.4%) patients developed complications in patients receiving homologous sealant while 11 (38.0%) patients had complication in autologous sealant group (P=0.711). Median duration of air leak was 3 days in two groups. Time to intercostal drain removal was 3.39 and 3.38 days in homologous and autologous sealant group respectively (P=0.978). Mean hospital stay was 5.5 days in patients receiving homologous sealant whereas it was 5.0 days in patients who had autologous agent (P=0.140). There were no significant differences between groups in terms of measured maximum air leak (P=0.823) and mean air leak (P=0.186). There was no significant difference in the incidence of complications between two groups (P=0.711). Conclusions: Autologous and heterologous fibrin sealants are safe and acts similarly in terms of air leak and hospital stay in patients who had resectional surgery.